2019
DOI: 10.1016/j.jcjd.2019.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Real-World Health Outcomes of Insulin Glargine 300 U/mL vs Insulin Glargine 100 U/mL in Adults With Type 1 and Type 2 Diabetes in the Canadian LMC Diabetes Patient Registry: The REALITY Study

Abstract: Key MessagesIn clinical trials, Gla-300 had similar glycated hemoglobin (A1C) reduction and a lower risk of hypoglycemia than Gla-100 in patients with type 1 diabetes (T1D) and type 2 diabetes (T2D). In a real-world clinical setting, insulin-naïve patients with T2D initiating Gla-300 or Gla-100 had similar A1C reduction and weight change.Patients with T1D or T2D switching to Gla-300 had significant reductions in A1C with no change in weight or insulin dose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 13 publications
4
23
0
Order By: Relevance
“…Our results therefore support the current American Diabetes Association (ADA)/European Association for the Study of Diabetes (EASD) consensus report for the management of hyperglycaemia in T2DM and the European summary of product characteristics for Toujeo® (IGlar U300), which state that a 10–14% [ 3 ] or 10–18% [ 8 ] higher dose of IGlar U300 versus IGlar U100 may be required to achieve similar glycaemic targets. Our results are also aligned with the results of randomised clinical trials and other real-world studies that have suggested that higher doses of IGlar U300 than IGlar U100 are needed to achieve a particular level of glycaemic control [ 11 , 18 , 24 26 ]. In many of these studies, as in the DosInGlar study, these patients with T2DM were insulin naïve when IGlar therapy was initiated [ 18 , 24 , 25 ].…”
Section: Discussionsupporting
confidence: 86%
“…Our results therefore support the current American Diabetes Association (ADA)/European Association for the Study of Diabetes (EASD) consensus report for the management of hyperglycaemia in T2DM and the European summary of product characteristics for Toujeo® (IGlar U300), which state that a 10–14% [ 3 ] or 10–18% [ 8 ] higher dose of IGlar U300 versus IGlar U100 may be required to achieve similar glycaemic targets. Our results are also aligned with the results of randomised clinical trials and other real-world studies that have suggested that higher doses of IGlar U300 than IGlar U100 are needed to achieve a particular level of glycaemic control [ 11 , 18 , 24 26 ]. In many of these studies, as in the DosInGlar study, these patients with T2DM were insulin naïve when IGlar therapy was initiated [ 18 , 24 , 25 ].…”
Section: Discussionsupporting
confidence: 86%
“…Similar findings were reported in retrospective observational studies such as SPARTA in the UK [14] and REALITY in Canada [18]. In the SPARTA study, the researchers investigated 300 T1DM patients who were switched to Gla-300.…”
Section: Discussionsupporting
confidence: 64%
“…Although the mean HbA1c at baseline was >9.0% and switching was performed to achieve improved glycemic control, the increase in basal insulin dose was only 2 U/ day and the mean reduction in HbA1c levels was 0.4%. In the REALITY study, the T1DM patients switching from Gla-100, neutral protamine Hagedorn, or detemir to Gla-300 showed similarly modest HbA1c reduction (−0.17%, from 8.35% to 8.18%) with a subtle basal insulin dose change (from 0.36 U/kg to 0.38 U/kg) during follow-up [18]. On the basis of the findings of these studies, physicians and patients may be balancing the improved glycemic control against the risk of nocturnal hypoglycemia.…”
Section: Discussionmentioning
confidence: 99%
“…Similar randomized trials of higher-dose insulin therapy, as typical for real-world conditions, have not been conducted. Recent studies of real-world clinical settings report mean daily basal insulin doses of close to 0.60 IU/kg in the Canadian REALITY Study for insulin-experienced patients with type 2 diabetes [ 124 ] and of 0.73 IU/kg in a physician survey in New York [ 125 ]. In the European multi-centre EU-TREAT Study, mean baseline insulin doses were between 32 and 54 U per day, depending on the type of insulin therapy regimen applied [ 126 ].…”
Section: Main Textmentioning
confidence: 99%